Comprehensive characterisation of individuals with fibrotic interstitial lung disease: baseline insights from the INJUSTIS study. - Khan,F; Stewart,I; Howard,L; Barber,CM; Borton,R; Braybrooke,R; Hearson,G; Jones,S; Maher,T; Matthews,L; Saini,G; Thompson,N; et al. (BMJ Open Respir Res, 2026)
BACKGROUND: Interstitial lung disease (ILD) represents a group of complex parenchymal conditions characterised by varying clinical trajectories. The It's Not JUST Idiopathic Pulmonary Fibrosis Study seeks to identify genetic, proteomic and clinical biomarkers that distinguish rapidly progressive fibrotic phenotypes from stable phenotypes irrespective of aetiology. This manuscript presents baseline insights from the recruited cohort. METHODS: In this prospective, longitudinal study, participants with fibrotic ILDs, including idiopathic pulmonary fibrosis (IPF), fibrotic hypersensitivity pneumonitis, rheumatoid arthritis-associated ILD, asbestosis and unclassifiable ILD, were enrolled from 24 UK sites. Participants underwent comprehensive baseline evaluation including demographics, exposure history, lung function testing, 6-min walk tests, blood sampling and standardised questionnaires to assess symptoms and quality of life. RESULTS: A total of 272 participants were recruited, predominantly older white males with a smoking history. Baseline lung function showed comparable forced vital capacity (mean 89.0% predicted), diffusion of carbon monoxide (mean 57.9% predicted) and 6-min walk distance (mean 302 m) across ILD subtypes. Hypertension was the most prevalent comorbidity, affecting 40.8% of participants, with no significant differences across subtypes. Anxiety and depression were notably lower in IPF than non-IPF (4.5%; 21.0%). Previous occupational exposure was reported in 68.8% of participants, with asbestos exposure the most prevalent (36%). Bird exposure was reported by 40.4% of participants, with no significant differences across subtypes. No significant differences in health-related quality of life scores were observed across subtypes. CONCLUSIONS: Despite varied aetiologies, fibrotic ILDs exhibit demographic and functional similarities, including lung function and health-related quality of life suggesting commonalities in disease mechanisms. TRIAL REGISTRATION